Clinical and health economic outcomes of alternative HER2 test strategies for guiding adjuvant trastuzumab therapy. (June 2011) - Lee, James A; Shaheen, Megan; Walke, Thomas; Daly, Matt
Aim: To evaluate the clinical outcomes and cost––effectiveness of human epidermal growth factor receptor 2 (HER2) testing strategies to guide adjuvant trastuzumab (AT) therapy in women with HER2-positive breast cancer.Methods: A literature review produced 72 studies comparing HER2 test methods, and we computed concordance (assuming fluorescence in situ hybridization [FISH] as a reference assay) to assess performance relative to American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) guidelines. An economic analysis provided cost––effectiveness of alternative strategies, including a Monte Carlo simulation to vary key assumptions such as test price and performance.Results: Of 46 studies comparing immunohistochemistry (IHC) and FISH, only seven met the ASCO/CAP guideline of 95% or better concordance. A total of 14 out of 21 studies comparing chromogenic in situ hybridization and three out of five studies comparing silver-enhanced in situ hybridization met the guideline. Confirmation of IHC 2 + and 3 + and primary FISH strategies are likely to reduce costs and improve quality of life relative to confirmation of IHC 2 + only. Initial testing with a gene amplification-based assay is probably a cost-effective alternative to confirmation of IHC 2 + and 3 + . The results are not sensitive to varying test price but are sensitive to test accuracy below 98%.Conclusion: Using a primary gene amplification-based assay to guide AT therapy for HER2-positive breast cancer probably results in lower US medical costs, increased life-years and increased quality of life compared with confirmation of IHC 2 + with a gene amplification-based assay. We recommend the ASCO/CAP guidelines reflect 98% or greater concordance relative to a reference assay. Additional research regarding therapy response is required to further differentiate between gene amplification-based assays.